The Closing Conversation Strategies In Indonesian Television Program - Agwin Degaf (Journal of English Language Teaching and English Linguistics, 2016)
This paper aims at exploring the use of closing utterances in conversation in one of Indonesian television program. The results show that there are three types of strategies implemented close conversation and all of it is the part of positive face-saving strategies. These three strategies are: positive comment, excuse (reason), and the imperative to end strategy (imperative to end the conversation). Positive comments applied if the speakers actually enjoy the conversation, but he or she had to end it for some reasons. Excuse strategy is used to close the conversation by providing an alternative motivation or alternative explanations for the hearer which potentially exposed to the threat of the face. Lastly, imperative to end the conversation strategy applied by the use of imperative words/sentences to close the conversation, but the speaker still trying to save his/her partner’s face. In general, the positive face-saving strategies used by speakers to close the conversation also consider the feelings of the hearer, giving positive comments or express a reason why a conversation should end. Key words: Closing Conversation Strategies, Indonesian Television Program